A ZnTa2O6 photocatalyst synthesized via solid state reaction for conversion of CO2 into CO in water. Issue 13 (16th March 2016) - Iguchi, Shoji; Teramura, Kentaro; Hosokawa, Saburo; Tanaka, Tsunehiro
Abstract : The photocatalytic activity of ZnTa2 O6 for the conversion of CO2 using H2 O as a reductant was demonstrated. CO was produced as a reduction product of CO2 in the presence of a Ag cocatalyst, accompanied by a stoichiometric amount of O2 evolution. Abstract : Because of the environmental problems and the resulting exigent demand for CO2 recycling processes, great attention is being paid to the photocatalytic conversion of CO2 into useful chemicals such as CO, HCOOH, HCHO, CH3 OH, and CH4 . We have previously reported that the Ag-loaded, Zn-modified Ga2 O3 photocatalyst exhibits excellent photocatalytic activity required for the conversion of CO2 into CO by using H2 O as a reductant and that the Ag particles that exist together with the Zn species act as good cocatalysts for the selective formation of CO. In this study, we demonstrated the photocatalytic activity of ZnTa2 O6 under UV light irradiation, which was prepared via solid-state reaction, for the conversion of CO2 in an aqueous NaHCO3 solution. A Ag cocatalyst-loaded ZnTa2 O6 photocatalyst evolved CO as a reduction product of CO2 with 46% selectivity toward CO evolution among the reduction products. In contrast, when Pt and Au were introduced as cocatalysts, the ZnTa2 O6 photocatalyst evolved H2 with high selectivity (>99.9%).